Pancasila sebagai Fondasi Ideologi dalam Reformasi Hukum Pidana terhadap Tindak Pidana Korupsi dan Terorisme - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Fadilah Isnaini Rahayu; Hayu Diva Lintang; Andreyan Ahmad Dani (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
This research analyzes the role of Pancasila in criminal law reform in Indonesia, particularly in relation to corruption and terrorism. Using a normative juridical approach and qualitative analysis of regulations, court decisions, and scientific literature, this research also applies the case study method. Data was collected through official documents and interviews with legal experts and law enforcement. The results revealed a gap between Pancasila values and existing legal practices, with challenges especially in fair law enforcement. The research highlights the need for community participation and strengthening the integrity of public officials for successful reform, as well as the importance of a holistic approach that includes legal education and continuous policy evaluation.